Intercultural Communication Apprehension and Emotional Intelligence in Higher Education: Preparing Business Students for Career Success. Issue 4 (December 2013) - Fall, Lisa T.; Kelly, Stephanie; MacDonald, Patrick; Primm, Charles; Holmes, Whitney
Given the expanding globalized workforce, business educators continue to seek new ways to prepare students for intercultural encounters. Although immersion in other cultures is the optimal strategy, this method is not always feasible. As such, educators seek other mechanisms to simulate intercultural experiences. This study examines emotional intelligence as a predictor of intercultural communication apprehension among university students ( N = 425). Results indicate that three of the emotional intelligence subscales predict intercultural communication apprehension: emotionality, sociability, and self-control. These results support the premise that emotional intelligence manages and/or reduces intercultural communication apprehension and therefore should be integrated in business curriculum.